Reaction of guava cultivars to Pratylenchus brachyurus. Summa Phytopathologica - Pereira, Kerly Cristina; Soares, Pedro Luiz Martins [UNESP]; Dos Santos, Jaime Maia [UNESP]; Felisberto, Patrícia Aparecida de Carvalho [UNESP] (FapUNIFESP (SciELO), 2018)
The root lesion nematode (Pratylenchus brachyurus) has been found in guava plants; however, there is no information in the literature about whether the crop is a potential host or is damaged due to parasitism by this nematode. The aim of this study was to evaluate, under greenhouse conditions, the development of the guava tree cultivars Paluma, Pedro Sato, Século XXI and Tailandesa inoculated with P. brachyurus. Furthermore, inoculated plants were compared with non-inoculated ones. Evaluations of height, stem diameter, fresh mass of aerial parts, fresh mass of roots, nematode population in the roots, as well as visual aspect, were performed at six and twelve months after inoculation. According to the obtained results, cultivars Pedro Sato, Século XXI and Tailandesa are not good hosts to P. brachyurus; however, Paluma is a good host. Tailandesa presented the best development of stem diameter, fresh weight of aerial parts and fresh weight of roots, relative to the other cultivars. Paluma is susceptible and intolerant to P. brachyurus; Século XXI is resistant and intolerant to P. brachyurus; Pedro Sato is resistant and intolerant to P. brachyurus, and cultivar Tailandesa is resistant and tolerant to P. brachyurus.
Reação de cultivares de goiabeiras à pratylenchus brachyurus
Keywords: Hostability; Psidium guajava; Reproduction factor; Root lesion nematode